The Impact of Monetary Policy on Household Leverage: Does Financial Literacy Matter? - Xuezhao Chen; Chenyi Kang; Haochang Yang; Zhenya Zhang; Shijia Kang (SAGE Open)
The rapid increase in household leverage in China has led to potential financial risks and threatened socio-economic stability. In mitigating household debt risks, the effectiveness of monetary policy regulation varies significantly with differences in household financial literacy. Based on micro-level household financial data from China, this paper delves into the impact of monetary policy on household leverage and its underlying mechanisms and analyzes the role of financial literacy in the transmission of monetary policy. The findings reveal that expansionary monetary policy helps reduce household leverage, while contractionary monetary policy leads to an increase. Monetary policy affects household leverage through the “income effect,”“wealth effect” and “substitution effect.” Notably, low financial literacy amplifies the impact of contractionary monetary policy on leverage, whereas high financial literacy mitigates this effect. This paper suggests strengthening financial regulation and risk warning systems, optimizing the design of monetary policy transmission, promoting multi-tiered financial product supply, and deepening the promotion of financial literacy education to achieve an effective balance between “stable growth” and “risk prevention.”